A portable air-quality station based on thick film gas sensors for real time detection of traces of atmospheric pollutants. Issue 1 (January 2016) - Fioravanti, A; Bonanno, A; Gherardi, S; Carotta, M C; Skouloudis, A N
Abstract: Different functional materials, single or mixed nano-crystalline semiconductor oxides, were synthesized via appropriated wet-chemistry routes. The powders were used to fabricate metal oxide (MOX) thick film gas sensors. Portable monitoring stations based on the aforementioned sensors were prepared, including electronics for acquisition, processing and wireless transmission of the data. Results of long term trials in field, carried out locating few units closely to as many conventional fixed-site monitoring stations, have been reported. The comparison was performed between the temporal evolution of the conductivity changes of the sensors with the pollutants' concentrations, as measured by the analytical instruments.